2017
DOI: 10.18632/oncotarget.20664
|View full text |Cite
|
Sign up to set email alerts
|

Cofilin 1 promotes bladder cancer and is regulated by TCF7L2

Abstract: Earlier reports demonstrated that Cofilin expression is increased in bladder cancer samples, though its function remains unknown. Here, we found that Cofilin 1 expression was higher in bladder cancer tissues than in paracancerous tissues. Overexpression of Cofilin 1 promoted, while Cofilin 1 knockdown inhibited, proliferation, migration, and invasion in the T24 and RT4 bladder cancer cell lines. In addition, Cofilin 1 overexpression increased, while Cofilin 1 knockdown decreased, bladder tumor volumes in mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 38 publications
4
13
0
2
Order By: Relevance
“…By CCK8 and clone formation assays, we found that shRNA lentivirus-mediated cofilin-2 silencing inhibited the proliferative activity of CNE-2R cells at different radiation doses. Wang et al showed that downregulation of cofilin 1 could inhibit cell proliferation in the human bladder cancer RT4 cell line [ 39 ], corroborating our findings. Cofilin promotes apoptosis in gastric cancer BGC-823 and SGC-7901 cells via mitochondrial translocation and induces mitochondrial damage and cytochrome c release; therefore, it may be a key target for the treatment of gastric cancer in the future [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By CCK8 and clone formation assays, we found that shRNA lentivirus-mediated cofilin-2 silencing inhibited the proliferative activity of CNE-2R cells at different radiation doses. Wang et al showed that downregulation of cofilin 1 could inhibit cell proliferation in the human bladder cancer RT4 cell line [ 39 ], corroborating our findings. Cofilin promotes apoptosis in gastric cancer BGC-823 and SGC-7901 cells via mitochondrial translocation and induces mitochondrial damage and cytochrome c release; therefore, it may be a key target for the treatment of gastric cancer in the future [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…Cofilin promotes apoptosis in gastric cancer BGC-823 and SGC-7901 cells via mitochondrial translocation and induces mitochondrial damage and cytochrome c release; therefore, it may be a key target for the treatment of gastric cancer in the future [ 40 , 41 ]. In addition, studies have shown that cofilin inhibition or silencing increases cell apoptosis in human bladder cancer RT4 cells and resistant HCC cells [ 39 , 42 ]. ShRNA-mediated knockdown of cofilin-2 enhanced apoptosis in CNE-2R cells, as demonstrated by flow cytometry in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The present study verified that DADS gradually decreased the mRNA and protein expression, as well as the phosphorylation of cofilin 1 in HL-60 cells in a time-dependent manner. Cofilin-1, an actin depolymerizing factor (ADF)/cofilin superfamily member, has been shown to be highly expressed in a number of cancer types and is associated with proliferation, migration, invasion, differentiation, metastasis and poor prognosis (16,21). The expression level of cofilin and its subcellular distribution play important roles in the high migratory ability of tumor cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…Актин-связывающие белки, кроме обеспечения локомоции, ассоциированы с другими клеточными процессами: пролиферацией, апоптозом, эндо-и экзоцитозом. Важное значение в развитии злокачественных опухолей принадлежит актинсвязывающим белкам: кофилину, профилину, эзрину, фасцину и аденилил-циклаза ассоциированному протеину 1 (САР1) [3][4][5][6][7][8][9]. Основная функция САР1 у эукариот -регуляция реконструкции актина в ответ на клеточные сигналы.…”
Section: Introductionunclassified